Real-time pipeline monitoring with FSR sensors: an IoT wireless sensor network approach to multi-leak detection - Yilmaz Salman, Meric; Hasar, Halil (Iwa Publishing, 2025)
The increasing scarcity of potable water resources, exacerbated by climate change and aging urban infrastructure, has intensified the demand for real-time monitoring and detection of water losses in distribution networks. Traditional leak detection methods often rely on single-point analysis and lack detailed information on the hardware and software architecture of proposed systems, limiting their scalability and applicability. In this study, a wireless sensor network (WSN) based on FSR sensors was designed and implemented, with a gateway forwarding data to a cloud platform for remote monitoring, to address these limitations. The proposed system integrates both hardware and software components, providing secure wireless communication and real-time monitoring of pressure variations along the pipeline. Experimental validation was conducted using a laboratory-scale prototype pipeline where multiple simultaneous leakage scenarios were created. Results demonstrated that the developed device reliably detected and differentiated leaks at varying flow rates and multiple points, with sensors closest to leakage sites exhibiting rapid pressure drops, while downstream sensors showed delayed but converging responses. These findings not only validate the effectiveness of FSR-based sensing for multi-leak detection but also highlight the advantages of combining IoT and WSN architectures for scalable and low-cost monitoring solutions.
Keywords: multi-leak detection; real-time monitoring; wireless sensor networks